Implementation of sit-stand desks as a workplace health initiative: stakeholder views. Issue 5 (29th August 2019) - Hall, Jennifer; Kay, Tess; McConnell, Alison K.; Mansfield, Louise
Abstract : Purpose: Prolonged workplace sitting can harm employee health. Sit-stand desks are a potential workplace health initiative that might reduce and break up the time office-based employees spend sitting in the workplace. However, little is known about the feasibility and acceptability of providing sit-stand desks. The paper aims to discuss this issue. Design/methodology/approach: The present study sought stakeholder employee views surrounding sit-stand desk implementation within two UK-based non-profit organisations with open-plan offices. This paper draws on qualitative semi-structured interviews with 26 stakeholder employees and 65 days of participant observations. Data were analysed using thematic analysis, and organisational cultural theory framed the study. Findings: Stakeholders employees' positioning of sit-stand desks as a workplace health initiative reflected their perceptions of the relationship between sit-stand desk provision, employee health and organisational effectiveness. Perceptions were shaped by the nature and context of the organisation and by occupation-specific processes. Relatively fixed (e.g. organisational structure) and modifiable (e.g. selecting products compatible with the environment) factors were found to restrict and facilitate the perceived feasibility of implementing sit-stand desks. Practical implications: The findings offer several recommendations for workplaces to improve stakeholder employee attitudes towards sit-stand desk provision and to increase the ease and efficiency of implementation. Originality/value: Whilst extant literature has tended to examine hypothetical views related to sit-stand desk provision, this study consulted relevant stakeholders following, and regarding, the sit-stand desk implementation process.